Germanium based photonic components toward a full silicon/germanium photonic platform. Issue 2 (June 2017) - Reboud, V.; Gassenq, A.; Hartmann, J.M.; Widiez, J.; Virot, L.; Aubin, J.; Guilloy, K.; Tardif, S.; Fédéli, J.M.; Pauc, N.; Chelnokov, A.; Calvo, V.
Abstract: Lately, germanium based materials attract a lot of interest as they can overcome some limits inherent to standard Silicon Photonics devices and can be used notably in Mid-Infra-Red sensing applications. The quality of epitaxially grown intrinsic and doped materials is critical to reach the targeted performances. One of the main challenges in the field remains the fabrication of efficient group-IV laser sources compatible with the microelectronics industry, seen as an alternative to the complexity of integration of III-V lasers on Si. The difficulties come from the fact that the group-IV semiconductor bandgap has to be transformed from indirect to direct, using high tensile strains or by alloying germanium with tin. Here, we review recent progresses on critical germanium-based photonic components such as waveguides, photodiodes and modulators and discuss the latest advances towards germanium-based lasers. We show that novel optical germanium-On-Insulator (GeOI) substrates fabricated by the Smart Cut™ technology is a key feature for future Si - Complementary Metal Oxide Semiconductor (CMOS) - compatible laser demonstration. This review hints at a future photonics platform based on germanium and Silicon.